Persepsi Siswa Terhadap Layanan Digital di Perpustakaan SMA Negeri 10 Padang - Azhari, Ainul; Asmara, Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe students' perceptions of digital services in the library of SMA Negeri 10 Padang. This study used a descriptive quantitative method. The population in this study were all 1,144 active students of SMA Negeri 10 Padang. The sampling technique used purposive sampling and obtained 92 respondents. The theory used in this study is the Technology Acceptance Model (TAM). The results show that SMA Negeri 10 Padang students have a positive perception of the use of digital services in the library. This is based on the results of data analysis on the perceived usefulness indicator, which obtained an average score of 3.05 and the perceived ease of use indicator, which received an average score of 3.22. Based on the average scores obtained, the perceived usefulness and perceived ease of use indicators are in the good category on an interval scale. This means that digital services in the SMA Negeri 10 Padang library are perceived positively by students in helping and facilitating information searches.